Electrodeposition of 4-Benzenesulfonic Acid onto a Graphite-Epoxy Composite Electrode for the Enhanced Voltammetric Determination of Caffeine in Beverages - Leonardo de A. Furtado; Mariana C. de O. Gonçalves; Carlos V. M. Inocêncio; Edilson M. Pinto; Daniela de L. Martins; Felipe S. Semaan (Journal of Analytical Methods in Chemistry)
Caffeine is widely present in food and drinks, such as teas and coffees, being also part of some currently commercialized medicines, but despite its enhancement on several functions of human body, its exceeding use can promote many health problems. In order to develop new fast approaches for the caffeine sensing, graphite-epoxy composite electrodes (GECE) were used as substrate, being modified by different diazonium salts, synthetized as their tetraflouroborate salts. An analytical method for caffeine quantification was developed, using sware wave voltammetry (SWV) in Britton–Robinson buffer pH 2.0. Detection limits for bare electrode and 4-benzenesulfonic modified electrode were observed circa 145 µmol·L−1 and 1.3 µmol·L−1, respectively. The results have shown that the modification shifts the oxidation peaks to lower potential. Kinetics of the reaction limited by diffusion was more expressive when caffeine was added to the solution, resulting in decreases of impedance, characterized by lower Rct. All results for caffeine determination were compared to a reference chromatographic procedure (HPLC), showing no statistical difference. Analytical parameters for validation were suitably determined according to local legislation, leading to a linear behaviour from 5 to 150 µmol·L−1; precision of 4.09% was evaluated based on the RDC 166/17, and accuracy was evaluated in comparison with the reference method, with recovery of 98.37 ± 2.58%.